Bacillus atrophaeus WZYH01 and Planococcus soli WZYH02 Improve Salt Tolerance of Maize (Zea mays L.) in Saline Soil - Hou, Yaling; Zeng, Wenzhi; Ao, Chang; Luo, Ying; Wang, Zhao; Hou, Menglu; Huang, Jiesheng (Frontiers in Plant Science, 2022)
With the increasing shortage of land resources and people’s attention to the ecological environment, the application of microbial fertilizer with natural soil microorganisms as the main component has attracted increasing attention in saline agriculture. In this study, two salt-tolerant strains, YL07 (Bacillus atrophaeus) and YL10 (Planococcus soli), were isolated from maize (Zea mays L.) rhizosphere soil with a saturated conductivity (ECe) of 6.13 dS/m and pH of 8.32 (Xinjiang, China). The effects of B. atrophaeus WZYH01 (YL07) and Planococcus soli WZYH02 (YL10) on the growth and development of maize (Zea mays L.) under salt stress (ECe = 5.9 dS/m) were further studied. The results showed that compared with uninoculation, inoculation with B. atrophaeus WZYH01 and Planococcus soli WZYH02 significantly improved maize growth performance, biomass yield, and antioxidant levels under salt stress, and the effect of Planococcus soli WZYH02 was more prominent than the effect of B. atrophaeus WZYH01. Moreover, inoculation with B. atrophaeus WZYH01 and Planococcus soli WZYH02 protected maize from salt stress by regulating plant hormone [IAA and abscisic acid (ABA)] levels and increasing nutrient acquisition. In addition, the tested strains were most efficient for maize growth and health, increasing the content of K+ accompanied by an effective decrease in Na+ in maize tissues. The transcription levels of salt tolerance genes (ZMNHX1, ZMNHX2, ZMHKT, ZMWRKY58, and ZMDREB2A) in inoculated maize were also dramatically higher than the transcription levels of the specified salt tolerance genes in uninoculated maize. In conclusion, B. atrophaeus WZYH01 and Planococcus soli WZYH02 can alleviate the harmful effects of salt stress on crop growth, thereby promoting sustainable agricultural development.